(untitled) (Boletín Epidemiológico Semanal, 2024)
Introduction: It is essential to know the disease burden of acute respiratory infection due to respiratory syncytial virus (RSV) before implementing preventive measures. The aim of this study is to describe the epidemiology of RSV infection and estimate its disease burden in Spain using the Acute Respiratory Infection Surveillance System (SiVIRA). Method: SiVIRA data were used to estimate primary care cases and hospitalisations due to RSV by age group in 2021-22 to 2022-23 seasons. SiVIRA-estimated hospitalisations were compared with data on hospital discharges due to RSV in 2016 to 2020 from the Minimum Basic Data Set (MBDS). Results: SiVIRA estimated a season average of 907,194 primary care cases and 29,081 hospitalisations due to RSV in Spain. Those aged <5 years accounted for 259,013 cases (28.6%) and 15,375 hospitalisations (52.9%), most commonly requiring invasive mechanical ventilation (6.9%) and intensive care unit (ICU) admission (14.4%). In those aged ≥65 years, 128,590 cases (14.2%) and 10,360 hospitalisations (35.6%) were estimated. In the extended MBDS analysis, 21,258 hospitalisations were observed in those aged <5 years (42.4%) and 22,758 in those aged ≥65 years (45.4%). Conclusions: The greatest impact of RSV infection occurs in those aged <5 years, particularly in those aged <1 year. The substantial hospital burden in older adults suggests that preventive public health measures should be considered. Estimates of hospital burden from SiVIRA surveillance were comparable to those from the extended MBDS analysis.